Efeito da clorexidina e flúor na resistência coesiva da estrutura dental irradiada e não irradiada - Neiva, Natalia Antunes (2010)
Radiation therapy significantly reduces the resistance of the tooth structure and the damage is potentially higher in the organic matrix. The use of products that promote the stabilization of collagen and / or agents to intensify the cross-links may provide less damage to the resistance of teeth irradiated. This study aimed analyze the effect of the use of chlorhexidine and sodium fluoride in the cohesive strength of the tooth structure during radiotherapy in head and neck believing that these products may influence the mechanical properties of enamel and dentin. Were collected 60 teeth divided into 2 groups, irradiated and non-irradiated, subdivided into 2 mouthwash protocols used 3 times a day: 0.12% chlorhexidine and 0.05% sodium fluoride and a control group. The specimens were evaluated by microtensile testing. The Tukey test (P <0.05) revealed that the presence of irradiation reduces the UTS of enamel, crown and root dentin regardless of the orientation of the prisms and tubules. The simulating of rinsing with chlorhexidine 0.12% recovered the resistance of crown dentin irradiated transversal to tubule orientation (GIP= 45,1 7,8 Ab), (GIT= 57,6 12,5 Aa), (GNIP= 76,2 12,5 Ab), (89,4 16,7 Aa) and the simulating of rinsing with sodium fluoride at 0.05% recovered the resistance of enamel irradiated making it similar to the non-irradiated enamel (GIP= 38,5 ± 4,9Aa), (GIT= 15,9 ± 2,7Aa), (GNIP= 43,2 ± 13,7Aa), (GNIT= 18,0 ± 2,0Aa). Therefore, the use of those substances for radiation treatment becomes essential to reduce the side effects and improve the quality of life of cancer patients in the head and neck.